School mediation to develop socio-emotional skills in university students of Early Childhood Education - Leon Medrano, Denisse Ivonne (2025)
This study evaluated the effect of a school mediation program, integrated into the curriculum, on the development of socio-emotional competencies in university students of Early Childhood Education. A quasi-experimental pretest-posttest design with a control group was implemented. The population consisted of a cohort of students, assigned to an experimental group that received an eight-week module based on micro-lessons, standardized simulations, and reflective journals, and a control group that followed the regular curriculum. Socio-emotional competencies were measured using a validated inventory, and mediation performance was assessed using an analytical rubric applied to simulations. The experimental group showed significant and substantial improvements in total socio-emotional competencies, with particularly notable gains in self-regulation and social awareness. A significantly higher performance was also observed on the mediation rubric, especially in the dimensions of emotional regulation and conflict understanding. A moderate positive correlation evidenced the relationship between the improvement in socio-emotional competencies and mediation performance. The curricular integration of school mediation, grounded in socio-emotional learning, proved to be an effective strategy for simultaneously developing the dispositional and procedural competencies required for conflict management in Early Childhood Education contexts, validating its relevance in initial teacher training.